Impact of low and high partial pressure of carbon dioxide on neuron-specific enolase derived from serum and cerebrospinal fluid in patients who underwent targeted temperature management after out-of-hospital cardiac arrest: A retrospective study. (August 2020) - Kang, Changshin; In, Yong Nam; Park, Jung Soo; You, Yeonho; Min, Jin Hong; Yoo, Insool; Cho, Yong Chul; Jeong, Wonjoon; Ahn, Hong Joon; Ryu, Seung; Lee, Jinwoong; Kim, Seung Whan; et al.
Abstract: Aim: In a previous study, low and high-normal arterial carbon dioxide tension (PaCO2 ) were not associated with serum neuron-specific enolase (NSE) in cardiac arrest survivors. We assessed the effect of PaCO2 on NSE in cerebrospinal fluid (CSF) and serum. Methods: This was a retrospective study. PaCO2 for the first 24 h was analysed in four means, qualitative exposure state (qES), time-weighted average (TWA), median, and minimum–maximum (Min–Max). These subgroups were divided into low (LCO2 ) and high PaCO2 (HCO2 ) groups defined as PaCO2  ≤ 35.3 and PaCO2  > 43.5 mmHg, respectively. NSE was measured at 24, 48, and 72 h (sNSE24, 48, 72 and cNSE24, 48, 72 ) from return of spontaneous circulation (ROSC). The primary outcome was the association between PaCO2 and the NSE measured at 24 h after ROSC. Results: Forty-two subjects (male, 33; 78.6%) were included in total cohort. PaCO2 in TWA subgroup was associated with cNSE24, 48, 72, while PaCO2 in the other subgroup were only associated with cNSE24 . PaCO2 and cNSE in qES subgroup showed good correlation ( r  = −0.61; p  < 0.01), and in TWA, median, and Min–Max subgroup showed moderate correlations ( r  = −0.57, r  = −0.48, and r  = −0.60; p  < 0.01). Contrastively, sNSE was not associated and correlated with PaCO2 in all analysis. Poor neurological outcome in LCO2 was significantly higher than HCO2 in qES, TWA, and median subgroups ( p  < 0.01, p  < 0.01, and p  = 0.02). Conclusion: Association was found between NSE and PaCO2 using CSF, despite including normocapnic ranges; TWA of PaCO2 may be most strongly associated with CSF NSE levels. A prospective, multi-centre study is required to confirm our results.